How Land Registration Affects Financial Development and Economic Growth in Thailand - Byamugisha, Frank (The World Bank, 1999)
November 1999 - Land registration in Thailand has significant positive long-run effects on financial development and economic growth. Using an economywide conceptual framework, the author analyzes how land registration affects financial development and economic growth in Thailand. He uses contemporary techniques, such as error correction and co-integration, to deal with such problems as time-series data not being stationary. He also uses the auto-regressive distributed lag model to analyze long lags in output response to changes in land registration. His key findings: -Land titling has significant positive long-run effects on financial development. -Economic growth responds to land titling following a J curve, by first registering a fall and recovering gradually, thereafter to post a long, strong rally. -The quality of land registration services, as measured by public spending on land registration, has strongly positive and significant long-run effects on economic growth. This paper - a product of the Rural Development and Natural Resources Sector Unit, East Asia and Pacific Region - is part of a larger effort in the region to increase the effectiveness of country assistance strategies in the area of property rights and economic development. The author may be contacted at fbyamugisha@worldbank.org